v. 1 - "Vora, Rajendra (ed.)" (New Delhi, 2002)
At the time of India's independence, the Prime Minister, Shri Jawaharlal Nehru, in famous 'tryst with destiny' speech had declared that once of the foremost aims of independent India was "the ending of poverty and ignorance and disease and inequality of opportunities". In the initial two decades after independence, it was believed that growth of the economy would reduce poverty through a trickle down effect.
Keywords: India - Social conditions